Cervical Carcinoma Manifesting as Progressive Bilateral Visual Loss - O’Sam Shibeeb; Paul Athanasiov; Sumu Simon; Jagjit Gilhotra (Case Reports in Ophthalmological Medicine)
We report a patient with bilateral choroidal metastasis from disseminated cervical squamous cell carcinoma. A 52-year-old woman presented with progressive bilateral visual loss due to choroidal masses in both eyes. The fundus examination revealed posterior serous retinal detachment in both eyes associated with creamy choroidal lesions. A thorough systemic work-up revealed choroidal metastasis from a squamous cell carcinoma of the cervix. This case highlights the importance of a thorough systemic evaluation in patients with choroidal tumours.